The Deteriorating Patient: Therapies Including Lung Transplantation - Detailleur, Stephanie; Vos, Robin; Goeminne, Pieter (Seminars in Respiratory and Critical Care Medicine, 2021)
In this review paper, we discuss the characteristics that define severe bronchiectasis and which may lead to deterioration of noncystic fibrosis bronchiectasis. These characteristics were used to establish the current severity scores: bronchiectasis severity index (BSI), FACED, and E-FACED (exacerbation frequency, forced expiratory volume in 1 second, age, colonization, extension and dyspnea score). They can be used to predict mortality, exacerbation rate, hospital admission, and quality of life. Furthermore, there are different treatable traits that contribute to severe bronchiectasis and clinical deterioration. When present, they can be a target of the treatment to stabilize bronchiectasis.One of the first steps in treatment management of bronchiectasis is evaluation of compliance to already prescribed therapy. Several factors can contribute to treatment adherence, but to date no real interventions have been published to ameliorate this phenomenon. In the second step, treatment in deteriorating patients with bronchiectasis should be guided by the predominant symptoms, for example, cough, sputum, difficulty expectoration, exacerbation rate, or physical impairment. In the third step, we evaluate treatable traits that could influence disease severity in the deteriorating patient. Finally, in patients who are difficult to treat despite maximum medical treatment, eligibility for surgery (when disease is localized), should be considered. In case of end-stage disease, the evaluation for lung transplantation should be performed. Noninvasive ventilation can serve as a bridge to lung transplantation in patients with respiratory failure.
Keywords: bronchiectasis; severity; treatment; lung transplantation